Interfering TAL effectors of Xanthomonas oryzae neutralize R-gene-mediated plant disease resistance - Zhiyuan Ji (Nature Portfolio, 2016)
The rice pathogen Xanthomonas oryzae produces TAL effectors (TALEs) that promote virulence. Here, the authors identify truncated TALEs that interfere with the function of a rice gene, Xa1, which confers resistance to all tested full-length TALEs.